The Hidden Years of Ælred of Rievaulx: The Formation of a Spiritual Master - Waddell, Chrysogonus (Cistercian studies quarterly, 2006)
The article discusses Gaetano Raciti's "Corpus Christianorum" edition of Saint Ælred's sermons after 1989. The first Advent sermon in the first Clairvaux collection was based on the gospel-pericope of Jesus' Palm Sunday entry into Jerusalem. On the other hand, the Durham collection contains thirty-two sermons and includes citations of antiphon-texts. The sermons in the Clairvaux collection cannot be distinguished on the score of style or theological content from any of Ælred's later sermons. He has attained to the maturity of the spiritual master as evident in his writings. His writings are remarkable for their doctrinal depth, pastoral relevance and simplicity of diction.